Analisis Kemampuan Berpikir Kritis Murid dalam Memecahkan Masalah pada Mata Pelajaran Matematika Kelas 3 Sekolah Dasar - Marina Dwi Kristanti; Mu’jizatin Fadiana; Heny Sulistyaningrum (STKIP Subang, 2026)
Critical thinking skills are essential 21st-century skills that must be instilled starting from elementary education, particularly in Mathematics. This study aims to describe the level of critical thinking skills of third-grade students at UPT SD Negeri Dikir in the subject of time units and to identify the influencing factors. The research method used is descriptive qualitative. The subjects consisted of 24 third-grade students. Data were collected through observation, interviews, and problem-based essay tests, and then analyzed using the Miles and Huberman interactive technique. The results showed that the students' overall critical thinking skills were in the very low category, representing 65% of the total population. Specifically, the indicators for basic clarification and analysis were in the moderate category, while the inference indicator (drawing conclusions) was in the low category. This low proficiency is influenced by external factors such as conventional teaching methods (lecturing), lack of variety in learning media, and insufficient stimulation from parents. Dominant internal factors include low learning motivation, poor reading interest, and limited understanding of the material. This study concludes that more interactive and contextual learning innovations are required to foster students' critical thinking skills from an early age.